2006
DOI: 10.1007/s00109-005-0029-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of L-type Ca2+ channels in iron transport and iron-overload cardiomyopathy

Abstract: Excessive body iron or iron overload occurs under conditions such as primary (hereditary) hemochromatosis and secondary iron overload (hemosiderosis), which are reaching epidemic levels worldwide. Primary hemochromatosis is the most common genetic disorder with an allele frequency greater than 10% in individuals of European ancestry, while hemosiderosis is less common but associated with a much higher morbidity and mortality. Iron overload leads to iron deposition in many tissues especially the liver, brain, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
155
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 186 publications
(168 citation statements)
references
References 185 publications
(327 reference statements)
7
155
0
2
Order By: Relevance
“…3,22 The pathological accumulation of iron in multiple tissues observed in iron overload conditions is thought to be caused by excessive influx of iron into plasma, as well as unbalanced erythrophagocytosis by reticuloendothelial cells in spleen and liver that lead to persistently high circulating NTBI levels which are responsible for the systemic iron dispersal. The hypothesis that tissue iron overload is caused by NTBI is largely based on the assumption that NTBI is randomly transported into cells by unregulated mechanisms, presumably via non-specific divalent cation transporters 23,24 or calcium channels, [25][26][27] subsequent to extracellular reduction of iron(III) to iron(II) by a cell-surface iron reductase such as Dcytb. Chronic exposure of cells in vitro to artificial iron complexes that presumably mimic NTBI (usually ferric citrate) [10][11][12]28,29 has been shown to generate cellular iron overload as indicated by increased ferritin levels, ROS generation, protein and DNA oxidation, and other indicators of cell damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,22 The pathological accumulation of iron in multiple tissues observed in iron overload conditions is thought to be caused by excessive influx of iron into plasma, as well as unbalanced erythrophagocytosis by reticuloendothelial cells in spleen and liver that lead to persistently high circulating NTBI levels which are responsible for the systemic iron dispersal. The hypothesis that tissue iron overload is caused by NTBI is largely based on the assumption that NTBI is randomly transported into cells by unregulated mechanisms, presumably via non-specific divalent cation transporters 23,24 or calcium channels, [25][26][27] subsequent to extracellular reduction of iron(III) to iron(II) by a cell-surface iron reductase such as Dcytb. Chronic exposure of cells in vitro to artificial iron complexes that presumably mimic NTBI (usually ferric citrate) [10][11][12]28,29 has been shown to generate cellular iron overload as indicated by increased ferritin levels, ROS generation, protein and DNA oxidation, and other indicators of cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in thalassemia or other iron overload disorders, it is not only difficult to experimentally simulate NTBI per se, but also to reproduce the possible chemical modifications of plasma components that become exposed to oxidative stresses due to a rise in labile iron and depletion of antioxidants. 29,30 Despite these limitations, attempts have been made to assess NTBI transport by using NTBI-simulating complexes of radiolabeled iron in protein free settings and by artificial inclusion of reductants in order to render the iron transportable by various voltage activatable Ca channels [25][26][27] or by a putative Zn transporter. 23,24 The pathophysiological significance of such approaches is still a subject of debate, and likewise the effects of Ca-channel blockers on ironassociated cardiac damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancy in these findings may be due to differences in the age of animal models. Neonatal myocytes have fewer L-type Ca 2+ channels with a smaller L-type Ca 2+ current than adult myocytes (52). It has been proposed that the Ca 2+ current investigated in cultured neonatal myocytes may be underestimated due to less density in beating cells and more myocyte death (52).…”
Section: Pathways Of Iron Entry Into Cardiomyocytesmentioning
confidence: 99%
“…Oudit et al (51) demonstrated that amlodipine and verapamil reduced intracellular iron accumulation and oxidative stress without disturbing diastolic and systolic function. L-type Ca 2+ channel blockers affect not only cardiomyocytes, but also pancreatic beta cells and anterior pituitary cells, which are important target cells for iron toxicity (52).…”
Section: Possible Future Therapeutic Modalitiesmentioning
confidence: 99%